Percepções de inclusão social entre idosos usuários e não usuários de serviços destinados à terceira idade - Silva, Mônica Ferreira da (2014)
A reduction in social contact among the elderly can result in unhealthy social isolation, and an increase in depressive symptoms. To combat this problem, services for the elderly are emerging, but little is yet known about the factors that affect the use of these services and the contribution of these programs to reduce social isolation. On the basis of the literature review, a new instrument was constructed to evaluate the extent to which older people who are engaged in activities outside the family circle feel that these involvements create opportunities to be more active, more competent, meet new people, form new friendships, learn new skills, do something they enjoy, or to do something related to their personal interests. The overall objectives of the current study were to: a) compare the perceptions of users and non-users of services for the elderly, with respect to their perceptions of the adequacy of their opportunities for social contact outside the family, and b) to determine if elderly people with more positive perceptions of these activities also report fewer depressive symptoms. Participants included 60 people aged 65 years or older (15 female and 15 male service users, and 15 female and 15 male non-users), all residing in a small city with approximately 122.000 inhabitants, in the interior of the state of São Paulo, Brazil. All respondents obtained scores equal to or above their cut-off score on the Mini Mental State Examination, such that all participants presented normal cognitive functioning. After signing the consent form, the participants responded to instruments about their financial status, physical and mental health (Brazilian Socioeconomic Criteria, Katz Scale of ADL, the PAQ and the Geriatric Depression Scale). Next, participants rated the extent to which their nonfamily activities meet their needs for social inclusion. The two groups were highly similar with respect to socioeconomic status, education, and functionality levels. The main findings indicate that both users and non-users of services for the elderly reported a high level of satisfaction with their non-family activities. In addition, average ratings of their opportunities for social inclusion were high in both groups, but those who used services for senior citizens had fewer depressive symptoms than those who did not use these services, which is coherent with some other studies that point to the positive effects of attending universities for senior citizens. As such, the primary contribution of this study was to initiate more detailed work, to identify and better understand how to create opportunities for the social inclusion of the elderly.